New modified Nafion-bisphosphonic acid composite membranes for enhanced proton conductivity and PEMFC performance - Teixeira, Fatima (2020)
Submitted by Paula Candeias (paula.candeias@lneg.pt) on 2020-09-24T13:22:46Z No. of bitstreams: 1 A2_TeixeiraRangel_IJHE_Feb2020.pdf: 1401668 bytes, checksum: 11a0dbf490235b45509f969aeebe3402 (MD5)